Syphilis in pregnancy and their influence on fetal and maternal morbidity: an integrative review (Research, Society and Development, 2022)
Aiming to identify the basic factors in the prevention of gestational syphilis and its maternal-fetal complications, an integrative literature review was carried out. Using the SciELO and LILACS databases, 22 articles published between the period 2006 to 2020 were selected, as well the data obtained after an intervention on the topic with pregnant women at the UBS in the Santa Rita neighborhood, in the city. of Imperatriz-MA. The basic factors in the prevention of gestational syphilis include measures to prevent the disease, adequate adherence to prenatal care for early diagnosis, institution of specific treatment, agreement of the pregnant woman to therapy and follow-up by a multidisciplinary health team after the condition. The promotion of knowledge about gestational syphilis and its complications both for pregnant women and for health professionals who assess and treat this group is essential for the prevention of this disease and its problems.